Characteristics of the existing methods for obtaining carotenes from carotenoid concentrates - E. V. Lisovaya; A. D. Achmiz; E. P. Viktorova; A. A. Skhalyakhov (Новые технологии)
Carotenes, which simultaneously have the properties of natural dyes and biologically active substances that have a positive effect on human health and life expectancy, are becoming increasingly widespread in the food, pharmacological and cosmetic industries. This necessitates an increase in the production of carotenes on an industrial scale. For use in food technologies, an encapsulated form of carotenes is recommended, which requires their high purity. The purpose of this study is to analyze domestic and foreign scientific, technical and patent information on existing methods for obtaining carotenes from carotenoid concentrates to determine the direction of research for the development of technology for the production of carotenes, in particular lycopene, ensuring the production of high purity lycopene from carotenoid concentrates, as well as increasing release of lycopene. The issues of using chromatographic methods for isolating lycopene, their advantages and disadvantages, as well as the use of non-polar and low-polar organic solvents for isolating lycopene from carotenoid concentrate are considered. The promising direction of research on the use of adsorption resins in the isolation of lycopene from carotenoid concentrates is noted.It has been concluded that the currently existing methods for obtaining carotenes from carotenoid concentrates, in particular lycopene, are quite technically complex and time-consuming. Some of the mallow the production of high purity lycopene, but the yield of lycopene is so low that their industrial scaling seems impractical. Taking this into account, research is being updated in the field of developing a technology for producing lycopene from a carotenoid concentrate, providing a high yield of high purity lycopene, with the possibility of its implementation on an industrial scale.